CHARACTERIZATION AND ESTERIFICATION OF VARIOUS WASTE FRYING OILS AS FEEDSTOCKS FOR BIODIESEL PRODUCTION (FUDMA JOURNAL OF SCIENCES, 2023)
The main objective of the study was to characterize and esterify ten waste frying oil (WFO) samples collected from fried food vendors and analyse their suitability as feedstock for biodiesel production. The parameters of the WFOs analyzed included; colour, odour, pH, specific gravity, kinematic viscosity (Oswald viscometer), moisture content (oven drying method), iodine value, acid value and saponification value. Esterification was carried out to lower the free fatty acid (FFA) contents of the waste frying oils. Mean values for specific gravity varied from 0.892±0.022 to 0.905±0.075 g/cm3. The mean kinematic viscosity of the WFOs ranged from 43.120 ±1.530 to 97.530 ±6.360 mm2/s. The mean acid value obtained varied from 2.730 ±0.404 to 16.956 ±3.806 mg/g while the mean free fatty acid concentration in the WFO ranged from 1.95 ±0.17 to 12.09 ±2.11 mg/g. Results indicated that WFOs used for frying fish may not be good feedstocks for biodiesel production since they contained the highest levels of FFA. Both refined and unrefined oils were used for frying in the sampling area. The foodstuffs fried in the oils included Akara (bean cake), yam, potato, plantain and fish. Duration of use of the oils ranged from 5 days to 3 weeks. After, esterification, only the free fatty acid contents of 4 samples were reduced below 0.5% by esterification while others ranged between 0.70% and 2.59%. Optimum conditions for the esterification were methanol: concentrated sulphuric acid ratio of 42:1; reaction temperature of 60oC; reaction time of 30 min with 5 min application of heat.
Keywords: Waste frying oil, feedstock, characterization, esterification